(untitled) (Pedagogical Horizons, 2025)
With the increasing use of artificial intelligence (AI) tools in scientific work, universities and colleges are faced with the task of developing precise guidelines for their responsible use. The question arises as to what guidelines for transparent documentation students and teachers should receive in order to ensure scientific integrity. The problem is that AI-assisted writing not only changes text production itself; the process of knowledge acquisition is also increasingly being questioned, as potential lack of transparency in documentation raises doubts about the extent to which deeper understanding actually takes place. This makes clear guidelines in the interests of transparency essential. This article discusses possible usage scenarios and examines the positions, legal information and documentation aids recommended by Austrian colleges and universities for responsible academic writing instruction with AI tools. The aim is to analyse AI guidelines to identify useful possibilities for AI use and examples of transparent documentation. The thesis is that, in addition to “traditional” writing didactics approaches, AI didactics support in university teaching is also necessary for good academic writing practice. The results show that process-oriented documentation that demonstrates the responsible use of AI can be the goal of sustainable preservation of good academic practice.